Longitudinal physical activity patterns and the development of cardiometabolic risk factors during adolescence - Aira Tuula; Kokko Sami Petteri; Heinonen Olli Juhani; Korpelainen Raija; Kotkajuuri Jimi; Parkkari Jari; Savonen Kai; Toivo Kerttu; Uusitalo Arja; Valtonen Maarit; Villberg Jari; Niemelä Onni; et al. (WILEY, 2025)
Purpose:
To examine the associations between longitudinal physical activity (PA) patterns and the development of cardiometabolic risk factors from adolescence to young adulthood.
Methods:
This cohort study encompassed 250 participants recruited from sports clubs and schools, and examined at mean age 15 and 19. Device-measured moderate-to-vigorous PA was grouped into five patterns (via a data-driven method, using inactivity maintainers as a reference). The outcomes were: glucose, insulin, homeostasis model assessment for insulin resistance (HOMA-IR), total cholesterol, HDL and LDL cholesterol, triglycerides, blood pressure, and body mass index (BMI). Linear growth curve models were applied with adjustment for sex, age, fruit/vegetable consumption, cigarette/snuff use, and change in the device wear-time.
Results:
Insulin and BMI increased among decreasers from moderate to low PA (beta for insulin 0.23, 95% CI 0.03-0.46; beta for BMI 0.90; CI 0.02-1.78). The concentration of HDL cholesterol decreased (beta -0.18, CI -0.31 to -0.05) and that of glucose increased (beta 0.18, CI 0.02-0.35) among decreasers from high to moderate PA. By contrast, among increasers, blood pressure declined (systolic beta -6.43, CI -12.16 to -0.70; diastolic beta -6.72, CI -11.03 to -2.41).
Conclusions;
Already during the transition to young adulthood, changes in PA are associated with changes in cardiometabolic risk factors. Favorable blood pressure changes were found among PA increasers. Unfavorable changes in BMI, insulin, glucose, and HDL cholesterol were found in groups with decreasing PA. The changes were dependent on the baseline PA and the magnitude of the PA decline.